FOOD IN NINETEENTH-CENTURY BRITISH HISTORY ([S.l.])
1 online resource
Keywords: In the long nineteenth century, significant developments occurred in science, technology and medicine which transformed food production and consumption. Coupled with this was the impact of the Industrial and Agricultural Revolutions. Developments in agricultural production meant that the rapidly growing British population conglomerated around urban areas could be fed. However, worsening public health conditions in British towns and cities, combined with social problems such as poverty, meant that nutritional and dietary health declined. This volume explores the foods that were eaten in nineteenth-century Britain.